HIKAYAT KALILAH DAN DAMINA: SEBUAH CERMINAN MODEL PENGAJARAN MORAL MELALUI CERITA HIKMAH - Dwi Apri Kurniawan (tuahtalino, 2020)
Moral problems become one of the challenges that must be faced by society today. As the currents of globalization develop, the noble values of culture and norms are fading in the younger generation now. Moral teaching is considered necessary to be instilled in various ways, one of which is through literary works. Hikayat Kalilah and Damina are one of the popular Malay classical literary works that are included as ancient manuscripts. The values of wisdom in this saga have their own moral message for their readers. As a reflection of moral teaching, the script of Hikayat Kalilah and Damina is part of past literary works that can be used as a source of human moral learning through wisdom stories. Moral is closely related to the limits that assess a human behavior in his life in society. Moral is also used as a benchmark to assess a person's actions in society, good or bad value. The stories in Hikayat Kalilah and Damina are an alternative moral teaching media that is suitable for children. Because the story which mostly revolves around animal figures or fables is one type of story that is very popular with children.